Oxidation of Aryl Alcohols by Morpholinium Fluorochromate(VI) on Silica Gel, a Selective and Efficient Heterogeneous Reagent - S. Zahra Sayyed-Alangi; H. Sajjadi-Ghotbabadi; Mohammed T. Baei; Sahar Naderi (E-Journal of Chemistry)
Morpholinium fluorochromate(VI), MFC, is easily synthesized by reacting morpholine to an aqueous solution of CrO3 and HF. This reagent selectively oxidizes aryl alcohols to their corresponding aldehydes and ketones under mild conditions. Moreover, it is inert towards aldehydes, ketons, oximes, thiols, sulfids, phenols, pyrans, trimethylsilanes, malonates and thioacetamides. The durability, reaction rate, ease of filtration and efficiency of MFC are considerably increased upon its absorption on silica gel.